MODELAGEM MATEMÁTICA: UMA EXPERIÊNCIA INVESTIGANDO A PASSAGEM DO TRANSPORTE PÚBLICO - Ribeiro Rodrigues Gaioti, Lidiane; Oliveira da Fonseca, Deborah; Corrêa Meireles, Amanda; Alves Adame, Maiara; Mistura Zanon, Jéssica (LINKSCIENCEPLACE, 2026)
This article presents an account of graduates in mathematics, whose objective was to describe the first experience of future teachers of mathematics with modeling. During the activity, the authors put themselves in perspective of students to experience the use of the method in the teaching-learning of mathematics. The theme chosen for the modeling project was "Public Transport", because, analyzing the value of the ticket paid in the course comprised up to the educational institution, the students inquired about the price paid. Given this, the interest arose in checking if the tariff is adequate. The implementation of the modeling project has given us more confidence in the application of this methodology in our classes. For in the future, when we are practicing the teaching profession, we can remember the moment of our experience - as students - and use this teaching methodology in order to motivate the students and make them more autonomous and active.